TiB2-modified PDC electrical solder joints for electrical interconnection in extreme environments. Issue 17 (1st September 2022) - Wu, Chao; Lin, Fan; Pan, Xiaochuan; He, Yingping; Chen, Guochun; Cui, Zaifu; Liu, Xianlong; Sun, Daoheng; Hai, Zhenyin
Abstract: The use of electrical solder joints for die attachment and interconnection in harsh environments remains a significant challenge. The interconnections between traditional metal solder joints and ceramic/semiconductor devices often fail during thermal cycling owing to mismatched coefficients of thermal expansion. In this study, TiB2 -modified polymer-derived ceramic (PDC) electrical solder joints were developed for electrical interconnections. Owing to the close contact between the PDC paste and the metal/ceramic/semiconductor, as well as the TiB2 percolation path formed inside the solder joint, the solder joint exhibited extremely low resistance and reliable electrical connection. Thermal cycling tests showed that the PDC solder joints had negative resistance temperature coefficients, excellent repeatability, and oxidation resistance up to 800 °C. After being oxidized at 800 °C for 24 h, the resistance at the solder joint only changed by 1.4 Ω. This solder joint can not only be used for metal devices but also for ceramic/semiconductor device electrical interconnections in harsh environments. Highlights: A TiB2 -modified PDC solder joint was developed for metal/ceramic/semiconductor device interconnections in harsh environments. The solder joint exhibited excellent thermal stability and high-temperature oxidation resistance. The feasibility of solder joints for thin-film sensor interconnections was verified.